FORMATION OF PROFESSIONAL CULTURE OF FUTURE SPECIALISTS OF FOLK ART CRAFTS - Kolisnyk-Humenyuk, Yuliya I. (Educological discourse, 2015)
The article focuses on the need to improve system of vocational education to train specialists that meet international standards. Examines the role of the professional culture, the aim of which is to raise overall culture of personality through: the formation of students' creative thinking; implementation of professional orientation of the content of education; disclosure of professional qualities; creation of conditions for development of personal qualities of future professionals of artistic specialization.